Kajian Kesiapan Pengguna Google Maps Sebagai Salah Satu Penerapan Sistem Transportasi Cerdas - Tamara Latifah Jasmine; Rohmad Kafidzin (Journal of Economics and Management (JECMA), 2023)
Information technology in this era can help the users to get what is needed. Measurement of technolgy readiness is necessary with Technology Readiness Index (TRI) approach, to aims determine the readiness level of using technology. On of the technolofy uses in transportation field is application of intelligent transportation system like google maps. A general problem of google maps uses is error reading map or instructions, is cause the user is at in wrong way, like the case of motorcyclist enter the toll road. The author will measure the user's readiness to use a google maps, of academic civitas in Politeknik Rukun Abdi Luhur amounts of 65 peoples, with TRI method measurement. The result is, there are final respondents is 59 peoples. Where, 39 peoples using the method of viewing the display on google maps. The result of TRI measurement indicate that respondents is at medium level which a kumulative value is 3,284. Need an advice to google maps users in using the voice feature to avoid losing focus when driving. Besides that, google maps users also can explore and learn many feature of google maps, like choosing to avoid the toll road for motrocycle